Juridical Overview of the Use of Smart Contracts in Indonesia as a Form of Artificial Intelligence Development - Muhammad Rizqon Baihaiqi; Siti Ummu Adillah; Dahniarti Hasana (Sultan Agung Notary Law Review, 2022)
Apart from the problems in terms of data security in the midst of blockchain-based business development in Indonesia, it turns out that another problem in smart contracts is that the use of Smart Contracts in Indonesia is actually still a discourse among legal experts regarding the validity of smart contracts. The aims of this research are: a) To find out and analyzeimplementation of the use of smart contracts in Indonesia; b) To know and analyzeobstacles in implementing smart contracts in Indonesia and their solutions; c) To know and analyzelegal remedies that can be taken in the event of a dispute between the parties in the smart contract; d) To find out examples of deeds inthe use of smart contracts in Indonesia as a form of artificial intelligence development." Researchers used normative research specifications with secondary data sources. Stages to find the target, then used the approach through legislation (statute approach). The results were juridical review of the use of smart contracts in Indonesia based on Article 1320 of the Civil Code.Article 1338 of the Civil Code explains that “all agreements made legally valid as law for those who make them”. One of the uses of smart contracts on Ethereum. Thereuem's smart contract has the name ERC20.Article 3 Regulation of the Commodity Futures Trading Supervisory Agency Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Market of Crypto Assets on the Futures Exchange, Bitcoin which can be traded on the Futures Exchange.Barriers to implementing Smart Contracts in Indonesia and their solutionsimplementing ISO-based Information Security Management or the simplest following the National Institute of Standards and Technology (NIST) framework. ISO 27001:2013 is the latest ISO 27000 series released in 2013. ISO 27001:2013.Article 30 Paragraph (3) in conjunction with Article 40 Paragraph (3) of Act No. 1 of 2008 concerning Information and Electronic Transactions.